Normative and practical theory of social policy science on the case of the „Family 500 plus program” - Szarfenberg, Ryszard (Problemy społeczne: Trwałość i zmienność w dynamicznej rzeczywistości. Księga jubileuszowa z okazji 45-lecia pracy naukowej i dydaktycznej Profesor Jolanty Grotowskiej-Leder, 2022)
The aim of the article is to fill a gap in the theory and philosophy of political science, in the area of social policy. It proposes a concept of social policy theory combining cognitive and practical dimensions. It consists of four types of theory: descriptive, explanatory, normative and practical. The last two will be discussed in more detail due to the fact that they are given less importance in the social sciences. Normative theory justifies statements about what social policy should be and thus makes it possible to evaluate it. Practical theory, on the other hand, makes it possible to translate the results of the application of other theories into the practice of work with social policy. Description, explanation and evaluation make it possible to make recommendations for change, and change-making theory makes it possible. The issues of normative and practical theory are shown on the example of the expert evaluation of the Family 500 Plus Programme and the practical conclusions that can be drawn from this case.